BangaSpeak: an example of app design for aphasia clients and SLP users. Issue 2 (3rd March 2016) - Messamer, Paula; Ramsberger, Gail; Atkins, Anthony
Abstract : Background : Mobile Technologies are pervading many areas of speech language therapy. A large number of apps have been developed for use by and for people with aphasia. Despite their availability, it's unclear which design principles were followed to create these apps and which users were targeted for these apps. Aims : The aim of this paper is to introduce the use of claims analysis as an approach for user-centred design for clients with aphasia and for the speech-language pathologists (SLPs) who treat them. We aim, through the use of a single worked-example, to show how claims can influence the design of a treatment app. Methods & Procedures : The paper is divided into two parts. Part 1 describes the claims analysis method we used to research SLP and client needs. Part 2 shows how claims were considered and integrated into the design of an app for speech-language therapy. This app, BangaSpeak, is offered as one example of how designers can simultaneously consider the needs of two different types of users: clients with aphasia and SLPs. Conclusions : This paper shows how development teams can capture the needs of users separate from requirements. Finally, it outlines the design of one app for use in aphasia treatments. We believe that this approach can serve as a model for other development teams to follow.